KD & Co. Service / Diana Martin... [et al] - Martin, Diana; Rendy Rojer, Anthony; Siti Noor lntan, K Lenas; Nowijah, Kaiben; Weji, Samiza; Dercy, Piansin (2015)
KD & Co. Service providing service of Kadazan Dusun race traditional stuffs such as music instrument, costume and the special in our business is the traditional Kadazan Dusun food because we are selling a frozen food for customers. By this business we are focusing on local and foreigner to learn about the Kadazan Dusun culture. Other than that, we are trying to gain profit to develop our business in the future in order to help the young generation to continue the Kadazan Dusun culture and to help maintaining the stability of economy to our country through tourism.